176 Evaluation of a novel threonine source for nursery pig diets. (30th November 2020) - Humphrey, Dalton; Becker, Spenser; Lee, Jason; Haydon, Keith; Greiner, Laura L
Abstract: Four hundred and eighty (PIC 337 X 1050, PIC Genus, Hendersonville, TN) pigs were used to evaluate a novel threonine source (ThrPro, CJ America-Bio, Fort Dodge, IA) for nursery pigs from approximately 7 kg to 20 kg. At weaning, pigs were sorted by gender and fed a common diet for one week. Upon completion of the first week, pigs were sorted into randomized complete blocks, equalized by weight, within 16 replications. Pigs were allocated to one of three dietary treatments: positive control (POS)-SID LYS:THR 0.60, negative control (NEG)-SID LYS:THR ≤0.46 and alternative threonine source (TEST)-SID LYS:THR 0.60. All other nutrients met or exceeded the NRC (2012) recommendations. Growth and intake data were analyzed using PROC MIXED procedure in SAS. The experimental unit was the pen. During the first 14 days, pigs fed TEST had similar ADG (0.417 vs. 0.414 kg/d, P=0.81) and G:F (0.977 vs. 1.030, P=0.18) compared to POS, and increased ADG (0.417 vs. 0.387 kg/d, P=0.01) and G:F (0.977 vs. 0.898, P=0.05) compared to NEG. Over days 14-28, pigs fed TEST had similar ADG (0.523 vs. 0.532 kg/d, P=0.49) and G:F (0.712 vs. 0.707, P=0.71) compared to POS, and increased ADG (0.523 vs. 0.479 kg/d, P=0.002) and G:F (0.712 vs. 0.627, P< 0.0001) compared to NEG. Overall (d 0 to 28), pigs fed TEST had similar ADG (0.466 vs. 0.474 kg/d, P=0.48) and G:F (0.808 vs. 0.816, P=0.55) compared to POS, and increased ADG (0.466 vs. 0.433 kg/d, P=0.002) and G:F (0.808 vs. 0.725, P< 0.0001) compared to NEG. ADFI was not significantly different across treatments for the entirety of the study. In conclusion, the replacement of L-threonine with a novel threonine source resulted in similar growth performance in nursery pigs from approximately 7 kg to 20 kg.